PENGEMBANGAN POWERPOINT INTERAKTIF BERBASIS PROBLEM BASED LEARNING DALAM MENDUKUNG PEMAHAMAN MAHASIWA FISIKA MENGENAI MEKANIKA LANGRANGE - Hidayah, Yuliani; Setiaji, Bayu (Charm Sains: Jurnal Pendidikan Fisika, 2024)
Learning media is a very important component in the teaching and learning process. The use of learning media must be the main point that is considered by the facilitator so that there is good, effective, efficient and fun interaction with students. Lagrange mechanics material is quite difficult for students to understand so it is necessary to develop different learning media. This research aims to create learning media in the form of interactive powerpoints based on PBL (Problem Based Learning) to support the understanding of physics students about Langrange Mechanics. This research uses the Research and Development (R & D) method with the main stages carried out are define, design, development, and disseminate with a 4D model. Data collection technique by providing a validation sheet to one of the expert lecturers and fourth semester students of the Department of Physics Education, Yogyakarta State University. The feasibility of interactive powerpoint based on PBL (Problem Based Learning) on Lagrange Mechanics material from four aspects, namely material, method & model, quality of media display and attractiveness got an average of 3.37 with a very decent category. Learning media in the form of interactive powerpoints based on PBL (Problem Based Learning) on Lagrange Mechanics material is an alternative in supporting the understanding of physics students. PBL (Problem Based Learning) based Powerpoint helps in solving problems in life so that it can improve the quality of learning and active involvement of students.